2016
DOI: 10.1039/c6ra04894c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the performance of transparent conductive oxide-less back contact dye-sensitized solar cells by facile diffusion of cobalt species through TiO2nanopores

Abstract: TCO-less DSSC using cobalt electrolyte in a novel device structure is proposed. Dye surface passivation of TiO2 nanoparticle (TN) spacer boosts bulky Co3+ ion diffusion. Dramatic enhancement in DSSC performance for dye surface passivated TN spacer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The electrochemical impedance spectra (EIS) measurement was performed following our previous article. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical impedance spectra (EIS) measurement was performed following our previous article. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…The molecular composition of Co­(bpy) 2+/3+ complexes and sensitizing dyes YD2-o-C8 and Y123 is presented in Figure . Electrochemical impedance spectroscopy (EIS) analysis was carried out following the previously published article . The corrosion study of the SS-mesh and Ti-sputtered SS-mesh was carried out employing scanning electron microscopy (SEM), JEOL, JCM6000, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…28 In our T-C-O-less B-C-DSC structure, usually, a porous polymer sheet (a PTFE film with 35 μm thickness) is utilized as a spacer to soak the electrolyte which is very thick, leading to limited diffusion of (Co 2+/3+ ) complexes. 29 In this present work, we are utilizing different nanoparticles of TiO 2 and ZrO 2 films with their relatively much thinner layer employed as a spacer with different particle sizes to enhance the diffusion of (Co 2+/3+ ) complexes. A small optical absorption by (Co 2+/3+ ) complexes in the region from 330 to 430 nm motivated us to utilize these as a redox mediator.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, one electron redox shuttles based on metal–organic Co­(II)/Co­(III) complexes have emerged as an obvious choice due to their simpler outer sphere one electron transfer kinetics and easy dye regeneration process, reducing the correlated loss of open-circuit voltage . Unlike iodine-based electrolytes, cobalt electrolytes bear positive surface charge exhibiting an obvious attractive interaction with the negatively charged TiO 2 , which demands the strict surface passivation. , This is the reason why many of the sensitizers working well with iodine-based electrolyte exhibit hampered photon harvesting when the same is being employed with cobalt electrolyte . It has been found that sensitizing dyes bearing multiple and long alkyl chains as a substituent in the main dye framework are capable of inhibiting back electron transfer from the TiO 2 to the redox shuttle and function well with the cobalt redox mediators.…”
Section: Introductionmentioning
confidence: 99%